Ambiguous Business Cycles, Recessions and Uncertainty: A Quantitative Analysis - Giulia Piccillo; Poramapa Poonpakdee (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper investigates the effects of uncertainty on the macro economy by replicating its micro effects on individual subjective beliefs. In our model, the representative household has smooth ambiguity preferences and is uncertain about which scenario the economy will be in the next period: normal growth or recession. We anchor the ratio of expected utilities between the two scenarios through the empirical macroeconomic uncertainty index. The higher the macroeconomic uncertainty is, the deeper the recession that the household is expecting. Our estimations demonstrate that the smooth ambiguity model with an appropriate level of ambiguity aversion outperforms the benchmark model with no uncertainty in fitting the US output growth rate, especially during recessions. This holds true even when tested with out-of-sample forecasts. Our analyses show that the effect of uncertainty on the representative household's beliefs aligns with the corresponding empirical literature. Moreover, the Global Financial Crisis was associated with an increase in both risk aversion and ambiguity aversion, while the Dot-com Crisis only affected risk aversion.
Keywords: E70; D80; D90; E10; E30; 330; behavioural macro; uncertainty; estimated DSGE models